Beyond Seed and Soil: Understanding and Targeting Metastatic Prostate Cancer; Report From the 2016 Coffey–Holden Prostate Cancer Academy Meeting. Issue 2 (28th September 2016) - Miyahira, Andrea K.; Roychowdhury, Sameek; Goswami, Sangeeta; Ippolito, Joseph E.; Priceman, Saul J.; Pritchard, Colin C.; Sfanos, Karen S.; Subudhi, Sumit K.; Simons, Jonathan W.; Pienta, Kenneth J.; Soule, Howard R.
Abstract : INTRODUCTION: The 2016 Coffey–Holden Prostate Cancer Academy (CHPCA) Meeting, "Beyond Seed and Soil: Understanding and Targeting Metastatic Prostate Cancer, " was held from June 23 to June 26, 2016, in Coronado, California. METHODS: For the 4th year in a row, the Prostate Cancer Foundation (PCF) hosted the CHPCA Meeting, a think tank‐structured scientific conference, which focuses on a specific topic of critical unmet need on the biology and treatment of advanced prostate cancer. The 2016 CHPCA Meeting was attended by 71 investigators from prostate cancer and other fields, who discussed the biology, study methodologies, treatment strategies, and critical unmet needs concerning metastatic prostate cancer, with the ultimate goal of advancing strategies to treat and eliminate this disease. RESULTS: The major topics of discussion included: the molecular landscape and molecular heterogeneity of metastatic prostate cancer, the role of the metastatic microenvironment, optimizing immunotherapy in metastatic prostate cancer, learning from exceptional responders and non‐responders, targeting DNA repair deficiency in advanced prostate cancer, developing and applying novel biomarkers and imaging techniques, and potential roles for the microbiome in prostate cancer. DISCUSSION: This article reviews the topics presented and discussions held at the CHPCA Meeting, with a focus on the unknowns and next steps needed to advance our understanding of the biology and most effective treatment strategies for metastatic prostate cancer. Prostate 77:123–144, 2017 . © 2016 Wiley Periodicals, Inc.